Microplastic Distribution and Dynamics Between Riparian Vegetation and Alaknanda River in the Himalayan Region - Bhatt, Vaishali; Arya, Prasant; Chauhan, Jaspal Singh (Aquatic Life Sciences, 2026)
Microplastic (MP) contamination in freshwater ecosystems is an emerging environmental concern, yet interactions between MPs and riparian macrophytes remain poorly understood, particularly in Himalayan river systems. This study provides a baseline assessment of MP surface entanglement across riparian macrophyte species, along with associated surface water and sediment, from River Alaknanda, Srinagar, Uttarakhand, India, sampled in June 2023. A total of 30 macrophyte, surface water, and sediment samples were collected and processed using extraction protocols integrating washing, oxidative digestion, density separation, stereomicroscopic analysis, and polymer characterization through ATR-FTIR spectroscopy. MPs were extensively detected on macrophyte surfaces, with species-specific normalized burdens ranging from 16.47 ± 2.59 to 273.86 ± 26.21 MPs/g dry weight. Kruskal-Wallis analysis revealed significant interspecific variation in normalized MP abundance (H = 25.73, p = 0.0023), with Chenopodium ambrosioides exhibiting significantly higher MP burdens than Conyza sp. and Equisetum sp. No MPs within the analytical detection range of 100 µm-5 mm were detected in digested plant tissues. Fibres were the dominant MP type in macrophytes and water, whereas fragments predominated in sediments, with white particles being most abundant across all matrices. Polymer analysis identified polyester, polyethylene, polypropylene, polyterephthalate, and polyethylene-vinyl acetate as dominant polymers. Strong compositional correlations among macrophytes, water, and sediment indicated similarities in MP characteristics across environmental matrices. These findings suggest riparian macrophytes as complementary matrices for freshwater MP monitoring. Despite methodological and spatial limitations, this study establishes a preliminary framework for incorporating riparian vegetation into freshwater MP monitoring and highlights the need for further investigations.